Metallogeny and Mineralization Potential of the Bazman Granitoids, SE Iran. Issue 3 (July 2016) - Ghodsi, Mohammad Reza; Boomeri, Mohammad; Bagheri, Sasan; Lentz, David; Ishiyama, Daizo
Abstract: The Mesozoic Bazman granitoids are located in Sistan and Baluchestan province, southeastern Iran. Geology of the study area consists of Carboniferous shale, sandstone, and limestone and Permian siltstone, shale, sandstone, limestone, and dolomite that were intruded by the Bazman granitoids. These granitoids include various phases of granite, granodiorite, quartz‐monzodiorite, monzodiorite, diorite, and gabbro. They are metaluminous to slightly peraluminous, reduced, calc‐alkaline and I‐type, and display geochemical characteristics of continental margin (ensialic) granitoids. In this paper, field, petrography, and geochemical data were used to discriminate the Bazman granitoids either as productive or barren granitoids. Although there are a few skarn‐related mineral occurrences adjacent to the Bazman granitoids, most exposed intrusions are not hydrothermally altered and mineralized. Rb/Sr, Zr/Hf, and K/Rb ratios indicate that the granitic magmas that formed most of the Bazman granitoids indicate that they are moderately evolved and have generally not undergone post‐magmatic hydrothermal activity. The Sm/Eu and Rb/Ba ratios and the concentrations of Rb, Ba, and Sr within the aforementioned granitoids show that the rocks are similar to the averages of granitoids devoid of Li, Be, U, Sn, W, and Ta deposits. The I‐type arc characteristics and other geochemical features of the Bazman granitoids show that they are not typical of parental magmas to Sn, W, Mo, and Zn mineralization, but are mainly fertile for Cu and Fe (Au) skarn‐related granitoids. Abstract : The Mesozoic Bazman granitoids in southeastern Iran are mainly metaluminous to slightly peraluminous, reduced, calc‐alkaline and I‐type. Although there are a few skarn‐related mineral occurrences adjacent to the Bazman granitoids, most exposed intrusions are not hydrothermally altered and mineralized. The Sm/Eu and Rb/Ba ratios and the concentrations of Rb, Ba, and Sr and other geochemical features of the Bazmzn granitoids show that they are not typical of parental magmas to Li, Be, U, Sn, W, Ta, Mo and Zn deposits, but are mainly fertile for Cu, Fe and Au skarn‐related granitoids.